Development of poster learning media using Pictorial Riddle method on the structure and function of plant tissue in SMA Negeri 3 Sinjai - Fitriana, Fitriana; Arif, Wiwin Pramita; Maulana, Andi (Universitas Islam Negeri Alauddin Makassar, 2023)
Better learning media can encourage students to think critically and focus on learning materials. This study aims to (1) find out how to develop poster learning media with the Pictorial Riddle method on the structure and function of plant tissue; (2) find out the validity of poster learning media with the Pictorial Riddle method on plant tissue structure and function; (3) find out the practicality Poster learning media using the Pictorial Riddle method on the structure and function of plant tissue; and (4) knowing the effectiveness of Poster learning media with the Pictorial Riddle method on the structure and function of plant tissue. This research method is development research (Research and Development) which refers to the ADDIE development model which consists of 5 stages, namely: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. Product development is tested through validity test, practicality test, and effectiveness test. The subjects in this study were 26 students of class XI MIPA 2 SMA Negeri 3 Sinjai. The research instrument was a media validation sheet to determine product validity data, student response questionnaires and educator response questionnaires to obtain product practicality data, as well as test items to obtain product effectiveness data. The results showed that the developed media had a level of validity, namely 3.78 (very valid), the level of practicality was based on an assessmentthe response of educators and students is 3.6 (very practical), and the test of student learning outcomes using poster learning media with the Pictorial Riddle method reaches 100% with an average value of 88 (very effective). So that the poster learning media with the pictorial riddle method is feasible to use because it has met the valid, practical, and effective criteria.